Evaluation of antimicrobial effect of nitrofurantoin against other intracanal medicaments: An in vitro study - K. Sripriya; Raichurkar Hemanth Kumar; B. V. Thimma Reddy; Uday Kumar Chowdary Birapu; Raghavendra Kumar Jadadoddi; Veronica Gunde (Endodontology, 2025)
Aim: The aim of this study was to compare the antimicrobial effect of nitrofurantoin with 2% chlorhexidine (CHX) gel, Metapex, and triple antibiotic paste (TAP) against Enterococcus faecalis and Candida albicans. Methods: A total of 104 extracted single-rooted teeth were taken and randomly divided into four groups with 26 (n = 26) in each based on the medicament used, i.e. Group 1: 2% CHX gel, Group 2: Metapex, Group 3: TAP, and Group 4: nitrofurantoin. Each group was further divided into two subgroups with 13 in each (n = 13) based on the inoculation of microorganisms, i.e., E. faecalis and C. albicans. Each specimen was inoculated with microorganisms depending on the group and then incubated for 21 days. Later, all the specimens were evaluated for baseline count and medicaments were placed in the canals. Finally, after 7 days, all the specimens were irrigated properly and the colony counting was done and compared with baseline count. Paired t-test, one-way analysis of variance test, and post hoc Tukey’s test were used for statistical analysis. Results: The maximum reduction in the number of colony-forming units (CFUs) was seen for Nitrofurantoin against E. faecalis. For C. albicans, TAP showed a greater reduction in the number of CFUs. Conclusion: Among four medicaments, nitrofurantoin had superior antibacterial activity against E. faecalis, whereas TAP showed superior antifungal activity against C. albicans.